Simulating cable fires in Fire Dynamics Simulator : Based on small scale testing in cone calorimeter - Zacharoff, Hugo (Luleå tekniska universitet, Byggkonstruktion och brand, 2021)
In a society increasingly more influenced by technology and electricity, electrical and computer cables will play a more vital role in humans’ everyday life. With an increasing number of cables being introduced into society, the risk of fires caused by or involving cables will increase and become a more common danger to property and human lives. The fire properties of cables are tested according to Standard EN 50399 where vertically mounted cables are exposed to a burner for 20 minutes. The present work consists of running simulations imitating the conditions of Standard EN 50399 for testing cables using a Computational Fluid Dynamics program called Fire Dynamic Simulator (FDS). The general idea was to test the material in small-scale and running simulations to verify how well simulated values corresponded to values from actual testing, providing a potential less costly method of predicting the correct Euroclass in the development phase of new cables. During a visit at RISE in Borås, material for testing and a script previously used for testing a module of EN 50399 in FDS were obtained from previous work. The FDS script was later altered by adjusting the meshes inside the model in an effort to reduce simulation time. This was done by prioritizing smaller grid cells in high activity areas and using large grid cells in low activity areas. To verify the function of the model on the current version 7.5.0 of the FDS software, simulations were run empty without modelling the cables. To validate the FDS-model, temperatures were measured at four heights using a resemble of plate thermometers and the results were compared to older temperature measurements from an actual experiment using plate thermometers in the apparatus used at RISE when testing in the EN 50399 apparatus. To obtain the material data necessary for FDS, the material used as cable sheeting (surrounding the conductive metal core) molded into thin square plates were tested using a cone calorimeter at Luleå University of Technology. Two tests were conducted ...